An Anonymous Authentication Scheme in VANETs of Smart City Based on Certificateless Group Signature - Yuanpan Zheng; Guangyu Chen; Liguan Guo (Complexity)
With the change of the network communication environment in vehicular ad hoc networks (VANETs) of a smart city, vehicles may encounter security threats such as eavesdropping, positioning, and tracking, so appropriate anonymity protection is required. Based on the certificateless cryptosystem and group signature ideas, this paper proposes a certificateless group signature anonymous authentication scheme for the VANETs of a smart city. In this scheme, it can implement the process of adding, signing, verifying, and revoking group members only by simple multiplication of the elliptic curve and synchronization factor technology, which shortens the length of the signature and improves the efficiency of the signature. From the proofs of correctness and security, we know that it does not only has anonymity and traceability of the group signature scheme but also has unforgeability and forward security. According to the performance verification, this scheme has lower calculation overhead and higher authentication efficiency.